Computer educators' perception of the utilization of online assessment in the Covid‐19 era - Lu, Shaohua; Eloanyi, Chekwube B.; Olelewe, Chijioke J. (Computer applications in engineering education, 2023)
The proliferation of ICT in today's world of work particularly in education has necessitated the need to assess lecturers' views of online assessment use in the covid‐19 era given the disruptions in face‐to‐face teaching and learning process. The study adopted a mixed research design. The population for the study was 84 computer educators made up of 40 males and 44 females from the four public tertiary institutions in Enugu State, Nigeria. Three research questions and two hypotheses guided the study. The instruments used for data collection were a structured questionnaire titled “Computer Educators' Perception of Use of Online Assessment” (CEPUOA) and a guided interview relating to the research questions. The internal consistency was determined using the Cronbach α reliability test which gave an index of .9. The data collected were analyzed using mean and standard deviation while the null hypotheses were tested using a t‐test at 0.05 level of significance. The findings of the study indicated that computer educators have a positive disposition toward the use of online assessment in conducting various assessment techniques such as tests/quizzes, semester examinations, and seminar/project evaluations. The findings of the study further showed that the utilization of online assessment techniques facilitates timely monitoring of students' progress, and the provision of immediate feedback to the learners helps in preparing students with digital skills required to function in the 21st‐century workplace, among others. In view of these, it was recommended that tertiary institutions should initiate workable policies that will encourage the effective use of online assessment by lecturers.